PENGARUH PERAN KEPALA SEKOLAH SEBAGAI MANAJER, PERAN KOMITE SEKOLAH DAN PROGRAM BANTUAN OPERASIONAL SEKOLAH TERHADAP MUTU PENDIDIKAN SEKOLAH DASAR NEGERI SE KECAMATAN PATEBON KABUPATEN KENDAL - Mauluvi Nazir; Ngasbun Egar; Ghufron Abdullah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The first formulation of this problem is whether there is an influence of the role of the principal as a manager on the quality of public elementary school education in Patebon District, Kendal Regency. The second is whether there is an influence on the role of the School Committee on the quality of public elementary school education in Patebon District, Kendal Regency. Furthermore, is there an influence of the School Operational Assistance Program on the quality of public elementary school education in Patebon District, Kendal Regency? Finally, is there an influence on the role of the principal as manager, the role of the school committee and the school operational assistance program on the quality of public elementary school education in Patebon sub-district, Kendal Regency? This type of research is quantitative research using a causality survey method with a quantitative correlation approach. The sample for this research was 137 State Elementary School teachers in Patebon District, Kendal Regency. Research data collection techniques were carried out using questionnaires. Analysis includes validity testing, reliability testing, assumption/requirement testing, and hypothesis testing. Research results 1) there is a positive and significant influence of the role of the school principal as manager on the quality of education with a significance value of 0.036<0.05. 2) there is a positive and significant influence between the role of the school committee on the quality of education with a significance value of 0.00<0.05. 3) There is a positive and significant influence of the school operational assistance program on the quality of education with a significance value of 0.013<0.05. 4) there is a positive and significant influence on the role of the school principal as manager, the role of the school committee, and the school operational assistance program on the quality of education, with a significance value of 0.00<0.05. The role of the school principal as a maximum manager, the role of a good school committee and good management of school operational assistance programs can have an impact on improving the quality of education.